On broken wings - Cleeton, Chanel (Cleeton, Chanel. Wild aces romance, 2017)
"A year after losing her husband, Joker, the squadron commander of the Wild Aces, Dani Peterson gets an offer from his best friend, Alex "Easy" Rogers, to help fix up her house. Dani accepts, and their friendship grows - along with an undeniable attraction. Racked by guilt for loving his best friend's widow, Easy's caught between what he wants and can't have. Until one night everything changes, and the woman who's always had his heart ends up in his arms. Yet as Easy leaves for his next deployment, he and Dani are torn between their feelings and their loyalty to Joker's memory. But when Dani discovers something that sends them both into a spin, the conflicted lovers must overcome the past to navigate a future together..."--Back cover.